Novel adenovirus encoded virus-like particles displaying the placental malaria associated VAR2CSA antigen. Issue 8 (22nd February 2017) - Andersson, Anne-Marie C.; Resende, Mafalda; Salanti, Ali; Nielsen, Morten A.; Holst, Peter J.
Highlights: Anchoring of ID1-ID2a to virus-encoded VLPs improves functional antibody responses. Virus-encoded VLP anchored ID1-ID2a efficiently primes ID1-ID2a protein boosts. Antibody binding specificities are increased by ID1-ID2a VLP anchoring using HA TM-CT. Abstract: The malaria parasite Plasmodium falciparum presents antigens on the infected erythrocyte surface that bind human receptors expressed on the vascular endothelium. The VAR2CSA mediated binding to a distinct chondroitin sulphate A (CSA) is a crucial step in the pathophysiology of placental malaria and the CSA binding region of VAR2CSA has been identified as a promising vaccine target against placental malaria. Here we designed adenovirus encoded virus-like particles (VLP) by co-encoding Simian Immunodeficiency Virus (SIV) gag and VAR2CSA. The VAR2CSA antigen was fused to the transmembrane (TM) and cytoplasmic tail (CT) domains of either the envelope protein of mouse mammary tumour virus (MMTV) or the hemagglutinin (HA) of influenza A. For a non-VLP incorporation control, a third design was made where VAR2CSA was expressed without TM-CT domains. In the primary immunogenicity study in Balb/c mice, VAR2CSA fused to HA TM-CT was significantly superior in inducing ID1-ID2a specific antibodies after the first immunization. A sequential study was performed to include a comparison to the soluble VAR2CSA protein vaccine, which has entered a phase I clinical trial (NCT02647489 ). The results revealed the induction of higher antibody responses and increased inhibition of parasite binding to CSA using either VAR2CSA HA TM-CT or VAR2CSA MMTV TM-CT as priming vaccines for protein double-boost immunizations, compared to protein prime-double boost regimen. Analysis of pooled serum samples on peptide arrays revealed a unique targeting of several epitopes in mice that had been primed with VAR2CSA HA TM-CT. Consequently, modification of VLP anchors is an important point of optimization in virus-encoded retroviral VLP-based vaccines, and adenovirus VLPs boosted by recombinant proteins offer hope of increasing the levels of protective VAR2CSA specific antibodies.